Rheological characterization of vinal gum, a galactomannan extracted from Prosopis ruscifolia seeds. (January 2018) - Busch, V.M.; Delgado, J.F.; Santagapita, P.R.; Wagner, J.R.; Buera, M.P.
Abstract: Prosopis ruscifolia (or vinal tree) is an abundant plant from Argentina semiarid areas, whose seeds contain a galactomannan type interesting gum: vinal gum. The aim of this work was to analyze the rheological behavior of vinal gum suspensions and the consequences of its interactions with commercial gums widely employed in the food industry. V inal gum aqueous suspensions were in good agreement with the Cox-Merz rule at concentrations lower or equal to 1% (w/w), which establishes an empirical relationship between complex and apparent viscosity. The flow curves of vinal gum could be defined only by two parameters -Newtonian viscosity (η0 ) and strain rate ( γ ˙ 0.1 )- and the shear-thinning behavior of vinal gum complied with the generalized curve for other polysaccharides. In mixtures with xanthan gum, vinal gum exhibited a synergistic relationship on its elastic behavior (at a total gum concentration of 1% (w/w)). On the other hand, vinal gum showed no synergism with κ- carrageenan or sodium alginate at the same total concentration of polymer. Apparent viscosity of v inal gum aqueous suspensions showed Arrhenius type dependence with temperature, as other galactomannans. The rheological behavior was not dependent on shear time, and the thickening power of vinal gum was slightly affected by pH and ionic strength changes. The present work provides detailed information on rheological characteristics of a non-traditional galactomannan extracted from an abundant and available source, being a starting point for possible applications of vinal gum as thickening and/or stabilizing agent in food, pharmaceutical, paper, textile, oil and cosmetics industries. Graphical abstract: Highlights: Aqueous suspensions of vinal gum at ≤ 1% (w/w) agreed with Cox-Merz rule. Rheological behavior of vinal gum showed no dependence with time. Vinal gum flow curves showed Arrhenius type dependence with temperature. Vinal gum thickening power was slightly affected by pH and ionic strength changes. Xanthan- vinal gums mix showed synergistic elastic response at 1% (w/w) of total gum.